FUNCTIONAL OUTCOMES OF OPEN VERSUS CLOSED TREATMENT OF UNILATERAL MANDIBULAR CONDYLAR FRACTURES - Asim, Muhammad Adil; Ibrahim, Muhammad Wasim; Javed, Muhammad umer; Zahra, Rubbab; Qayyum, Muhammad Umar (Journal of Ayub Medical College Abbottabad, 2018)
Background: Although mandibular condylar fractures are among the most common fractures of maxillofacial region, the ideal method for treatment of these fractures is still a controversy. The objective of this study was to compare functional outcomes of open vs closed treatment of unilateral mandibular condylar fractures. Methods: This study was carried out at Department of Oral and Maxillofacial Surgery, Armed Forces Institute of Dentistry, Rawalpindi. All patients, included in our study, were randomly put in open and closed treatment groups. Patients were assessed for maximal mouth opening, deviation of mandible on opening and occlusal status six months postoperatively. Maximal mouth opening was assessed by maximal interincisal distance, deviation of mandible on opening by calculating the midline discrepancy during mouth opening and occlusion was assessed by clinical examination according the modified criteria described by Singh V et al.Independent samples t-test was used to compare means of variables in open and closed treatment groups. Results: After six months of follow up the mean mouth opening was 36.39±4.72 mm in open treatment group while it was 33.74±4.72 mm in closed treatment group and difference was statistically significant. While deviation of mandible on opening was found to be 0.48±0.99 mm in open treatment group and 1.09±1.60 mm in closed treatment group. The mean occlusal disturbance was found to be 1.17±0.38 in closed treatment group while it was 1.10±0.30 in open treatment group. Conclusion: Open treatment of unilateral mandibular condylar fractures results in better functional outcomes particularly in terms of mobility of mandible (mouth opening). Keywords: Mandibular condyle; Temporomandibular joint; Maxillomandibular fixation; Open reduction; Internal fixation